Bioaktifitas Antibakteri Ekstrak Etanol Teripang Pasir (Holothuria scabra) terhadap Pertumbuhan Klebsiella pneumoniae Secara In Vitro - Fifit Ervitha; Sulastrianah Sulastrianah; Indria Hafizah (Halu Oleo University, 2015)
Holothuria scabra is one of the biota that commonly found in Southeast Sulawesi waters and traditionally use as a source food and medicine by local tribe. They also harvesting this species for exported to several countrywith high demand. Even this species have commmercially beneficience, but there is lack of publication about the bioactivity, especially H. Scabra derived from southeast Sulawesi. This study aims to determine secunder metabolite that contain in the extractand to examine antibacterial bioactivity of H. scabra ethanol extract againstKlebsiellapneumoniae by defining the Minimum Inhibitory Consentration. The method using an experimental with post test onlycontrol group design. The extraction is using maseration method and the extract then diluted and divided intoten concentration 100%, 50%, 25%, 12,5%, 6,25%, 3,125%, 1,56%, 0,78%, 0,39%, and 0,19%. The secunder metabolite was determined by using TLC and the MIC was determined by using dilution method. All consentration.As the result, TLC test showing positif result for alcaloid and triterpenoid and the nutrient broth starting to show no turbidity in concetration 0,78%. The conclusion of this study is ethanol extract of H. Scabra contain alkaloid and triterpenoid as secunder metabolite and the MIC was in 0,78% concentration.Keywords: Holothuria scabra, Klebsiella pneumoniae, MIC, alkaloid, terpenoid